The Use of Extracorporeal Membrane Oxygenation-Cardiopulmonary Resuscitation in Prolonged Cardiac Arrest in Pediatric Patients: Is it Time to Expand It?. Issue 9 (September 2017) - Absi, Mohammed; Kumar, Susheel TK; Sandhu, Hitesh
Abstract : Abstract: Extracorporeal membrane oxygenation was instituted as an aid to in-hospital cardiopulmonary resuscitation (E-CPR) nearly 23 years ago, this led to remarkable improvement in survival considering the mortality rate associated with conventional cardiopulmonary resuscitation (CPR). Given this success, one begins to wonder whether the time has come for expanding the use of E-CPR to outside hospital cardiac arrests especially in the light of development of newer extracorporeal life support devices that are small, mobile, and easy to assemble. This editorial will review recent studies on this subject and address some key guidelines and limitations of this evolving and promising technology.